Unveiling the Implicit Message: A Comprehensive Exploration of Qur'anic Democracy using Ma’na-cum-Maghza Approach - Al Baihaqi, Muhammad Dzilfikri (UIN Sunan Kalijaga Yogyakarta, 2022)
Democracy has become a subject of debate among Muslim intellectuals due to its non-primary source origin from Islam. The journey of democracy in the Islamic world is accompanied by both support and opposition. Nevertheless, this does not imply that the Qur'an is incapable of addressing these issues. Despite not being explicitly mentioned, the concept of democracy can be discerned through implicit messaging and the process of interpretation. One of the verses that encompasses this concept is QS. Ali Imran: 159. This article aims to unveil the implicit message by employing a contemporary verse interpretation approach known as mana-cum-maghza. This approach results in the identification of five elements that constitute Qur'anic democracy. Firstly, upholding divine values. Secondly, exhibiting a humanitarian and unifying attitude. Thirdly, implementing decisions that arise from conferences, which can take the form of regulations and power transfer (democratic in nature). Fourthly, adhering to legal sources that are applicable to all citizens. Lastly, entrusting specialized individuals with the responsibility of managing specific fields.